Źródła wiedzy o rolach małżeńskich - Przybył, Iwona (Wydawnictwo Naukowe UAM, 2001)
This paper shows the results of the author’s study carried out in 1999-2000 among 280 married people. The conclusions reached during the performance of research and analysis allow to state that the main sources of knowledge about marital roles are observations of parent’s way to perform marital roles, parent’s verbal instructions and making conversations with future spouse. It was discovered that women more frequently than men consider that mass-media are an important source of their knowledge. Family is a social group having a great influence on the genesis of knowledge about marital roles and it is the main pattern for young couples, especially when their parents remain in the happy, successfull relations.
Sources of knowledge about marital roles